Let's simplify each expression step by step:
-
\( \frac{2^3}{2^2} \): \[ \frac{2^3}{2^2} = 2^{3-2} = 2^1 = 2 \]
-
\( (2^2)^3 \): \[ (2^2)^3 = 2^{2 \times 3} = 2^6 = 64 \]
-
\( 2^8 \times 2^{-3} \): \[ 2^8 \times 2^{-3} = 2^{8-3} = 2^5 = 32 \]
-
\( \frac{2^2}{2^3} \): \[ \frac{2^2}{2^3} = 2^{2-3} = 2^{-1} = \frac{1}{2} \]
-
\( 2^{-2} \times 2^{-3} \): \[ 2^{-2} \times 2^{-3} = 2^{-2-3} = 2^{-5} = \frac{1}{32} \]
Here are the simplified results:
- \( \frac{2^3}{2^2} = 2 \)
- \( (2^2)^3 = 64 \)
- \( 2^8 \times 2^{-3} = 32 \)
- \( \frac{2^2}{2^3} = \frac{1}{2} \)
- \( 2^{-2} \times 2^{-3} = \frac{1}{32} \)